Necroptosis of nucleus pulposus cells involved in intervertebral disc degeneration through MyD88 signaling - Fan, Hong; Chen, Zhe; Tang, Hai-Bin; Shan, Le-Qun; Chen, Zi-Yi; Liu, Shi-Chang; Zhang, Yong-Yuan; Guo, Xin-Yu; Yang, Hao; Hao, Ding-Jun (Frontiers in Endocrinology, 2022)
ABSTRACT BACKGROUDN CONTEXT: Low back pain, affecting nearly 40% of adults, mainly results from intervertebral disc degeneration (IVDD), while the pathogenesis of IVDD is still not fully elucidated. Recently, some researches have revealed that necroptosis, a programmed necrosis, participated in the progression of IVDD, nevertheless, the underlying mechanism remains unclear. PURPOSE: To study the mechanism of necroptosis of Nucleus Pulposus (NP) cells in IVDD, focusing on the role of MyD88 signaling. STUDY DESIGN: The expression and co-localization of necroptotic indicators and MyD88 were examined in vivo, and MyD88 inhibitor was applied to determine the role of MyD88 signaling in necroptosis of NP cells in vitro. METHODS: Human disc specimens were collected from patients receiving diskectomy for lumbar disc herniation (LDH) or traumatic lumbar fractures after MRI scanning. According to the Pfirrmann grades, they were divided into normal (Grades 1, 2) and degenerated groups (4, 5). Tissue slides were prepared for immunofluorescence to assess the co-localization of necroptotic indicators (RIP3, MLKL, p-MLKL) and MyD88 histologically. The combination of TNFα, LPS and Z-VAD-FMK was applied to induce necroptosis of NP cells. Level of ATP, reactive oxygen species (ROS), live-cell staining and electron microscope study were employed to study the role of MyD88 signaling in necroptosis of NP cells. RESULTS: In vivo, the increased expression and co-localization of necroptotic indicators (RIP3, MLKL, p-MLKL) and MyD88 were found in NP cells of degenerated disc, while very l low fluorescence intensity in tissue of traumatic lumbar fractures. In vitro, the MyD88 inhibitor effectively rescued the necroptosis of NP cells, accompanied by increased viability, ATP level, and decreased ROS level. The effect of MyD88 inhibition on necroptosis of NP cells was further confirmed by ultrastructure of mitochondria shown by Transmission Electron Microscope (TEM). CONCLUSION: Our results indicated that the involvement of MyD88 signaling in the necroptosis of NP cells in IVDD, which will replenish the pathogenesis of IVDD and provide a novel potential therapeutic target for IVDD.